ANALISIS PENDAPATAN BUMDes RAMBAH MUDA JAYA DESA RAMBAH MUDA ROKAN HULU - Irwansyah, Reno (Jurnal Mahasiswa Prodi SI Akuntansi, 2013)
Income represent something that of necessary for company. Because of important income require to be done bookkeeping to know how far income which have been obtained from one period to next periodthis research is done by BUMDes that address in Rambah Muda village, District Of Rambah Hilir, Sub-Province of Rokan Hulu is called by BUMDes Rambah Muda Jaya. The Document is used is formal document by BUMDes Rambah such as Financial Statement and Household Budget of BUMDes.The methode of callecting data is book study technique namely collect various source of data and study books related to cause factor analysis fluctuate operating income him so that more understanding. And in this research of researcher use descriptive method namely depict the problem of which in fact happened at BUMDes Rambah Muda Jaya.The result is the cause of fluctuate factor income is factor of intern company which consist of the existence of company promotion, existence of donation, record-keeping of good financial statement, credit procedure, level of loan flower, loaning duration, level of fund which is contridute , company performance and also factor of ekstern which consist of economic factor of storey level and awareness of societyKeyword: Income, Ektern Factor, Intern Factor